Synthesis and characterization of PCL-PEG-PCL 5000-1000-500 tri block copolymer - Kishore, Rapolu (Asian Journal of Pharmaceutics (AJP), 2024)
Objective: The objective of this study was to synthesize novel, amphiphilic, triblock, biodegradable polycaprolactone-polyethylene glycol-polycaprolactone (PCL-PEG-PCL) (5000–1000–1000) copolymer through ring-opening polymerization of ε-caprolactone (CL) using PEG as an initiator for long-acting drug delivery and biomedical applications. Materials and Methods: The copolymers were synthesized through ring-opening polymerization of ε-CL using stannous octoate as the catalyst. The resulting copolymers were characterized by 1H nuclear magnetic resonance spectroscopy (NMR), 13C NMR spectroscopy to determine the composition and end group estimation, gas chromatography (GC) for residual solvent estimation, fourier-transform infrared spectroscopy (FTIR) for identification of functional groups, X-ray diffraction, thermogravimetric analysis, and differential scanning calorimetry to analyze the thermal properties. Results and Discussion: 1H NMR spectra revealed ethylene groups at 1.35, 1.69, 2.43, and 4.06 ppm in PCL, while PEG displayed methylene (CH2) groups at 3.8 ppm. In addition, the FTIR spectra of the PCL-PEG-PCL copolymer exhibited prominent bands at 1720cm-1, indicative of carboxylic ester, C=O and 1175cm-1, indicative of ether, C-O, confirming the successful synthesis of the copolymer. PEG triblock polymer end cap analysis and molar ratio of CL:PEG for synthesized triblock copolymer was found to be hydroxyl end cap and 91:09, respectively. The GC results of triblock polymer were free of dichloromethane and water content was 0.2%. The copolymer exhibited distinct peaks at diffraction angles (2θ) of 21.14°, 23.45°, 20.14°, 35.8°, and 12.15°. It demonstrates that the copolymer was presented in crystalline form. Conclusion: Based on the data obtained, concluded that the synthesized triblock copolymer provided an acceptable and appropriate novel polymer for long-acting drug delivery and various biomedical applications.